Five new species of the Afrotropical dark sac spider genus Messapus Simon, 1898 (Araneae: Corinnidae) - Haddad, Charles R.; Mbo, Zingisile (Zootaxa, 2015)
The Afrotropical dark sac spider genus Messapus Simon, 1898 (Corinnidae: Corinninae) currently only comprises two described species, the type species M. martini Simon, 1898 and M. natalis (Pocock, 1898), which have both recently been redescribed. The leg and setal morphology of Messapus is studied using scanning electron microscopy for the first time, for M. martini and M. tigris sp. n., and additional characters are provided to supplement a recent generic description. Five new species are described in the current paper: M. megae sp. n. (♂ ♀, from Zimbabwe), M. meridionalis sp. n. (♀, from South Africa), M. seiugatus sp. n. (♀, from Guinea), M. tigris sp. n. (♀, from Botswana and Namibia), and M. tropicus sp. n. (♂ ♀, from Democratic Republic of the Congo). All five species are arboreal spiders occurring on bark, lower foliage strata and the canopies of forest and savannah trees. An identification key to the seven species of the genus is provided.